The Influence of Transformational Leadership and Communication on Employee Performance - Jesi Melani Sidabutar; Senen Machmud; Imelda Megawati (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2024)
Evidence suggests that transformational leadership and effective communication can positively impact employee performance. Effective communication plays a crucial role in translating the vision and goals of transformational leaders into actionable plans and tasks for employees, which can positively impact employee performance. This research analyzes the impact of transformational leadership and communication on employee performance in one of the companies providing architectural, civil, mechanical, electrical, and environmental management consulting services in Bandung. The research method used is quantitative, with a descriptive and verification approach. The sample used was 100 employees of a staff company engaged in Bandung's architectural, civil, mechanical, electrical, and environmental management services. We tested the data using validity and reliability tests and then analyzed it using path analysis. Research results indicate that transformational leadership and communication significantly influence employee performance. Transformational leadership and communication influence 81.0% of employee performance, while the remaining 19.0% is caused by other variables or factors that were not researched. This research focuses on transformational leadership and effective communication to improve employee performance. It contributes to increasing effectiveness and communication, which has implications for improving employee performance, especially in the environmental management consulting services sector. By investing in leadership development and promoting effective communication strategies, organizations can create an environment that maximizes employee potential and enhances performance. This research only discusses transformational leadership and effective communication to improve employee performance. However, several factors can still enhance performance, and this research only uses a small sample, so the results cannot be generalized.